Are mouse noodles actually made from mice? touring street food name translations - Zhu, Hongxiang; Ang, Lay Hoon; Mansor, Nor Shahila (Springer Nature, 2024)
Street food helps to characterise Southeast Asia as a popular gastronomic destination for tourism. However, confusion regarding its translation can make it difficult to understand the nature of its food types and selections. This study aims to examine how street food names in Malaysia are translated from Chinese to English and explore the cultural influence found within the translations of street food names. This study adopts a qualitative case study with thirty-six types of translations for mouse noodle, nineteen types for Hokkien Mee, twenty-two types for Wan Tan Mee, and seven types for Kueh Chap. Data analysis encompassed both the micro content analysis for food translation techniques with changes in content and linguistic aspects of translation varieties and the macro-analysis from an ethnography approach with a semi-structured interview comprised of perspectives from ten food vendors and twenty consumers. The analysis of the interviews is guided by linguistic and cultural factors. This study found that street food names were translated with transliteration, literal translation, amplification, omission, and their combinations—the results showed that transliteration was the most frequently used technique. In detail, the changes made in the translations were in both content and linguistic aspects—mainly addition, omission, restructuring, lexical, and morphological changes. The results also showed that the factors that played a major role include knowledge (background knowledge and linguistic competence), time, and culture (localisation and cultural policy). The ethnographic description explained how these factors result in transliteration within the social relations of Chinese Malaysians. In conclusion, the transliteration based on Chinese dialects and its varieties in spelling has labelled Malaysia a multicultural destination, in which its diverse cultures are intermingled in the translations of street food names.